The Effect of Learning Methodology and Personality Type on Cognitive Abilities - Rusdiyani, Isti (Indonesian Journal of Early Childhood Education Studies, 2016)
This research aims to understand the influence of learning methods and type of personality on children cognitive ability, in group B kindergarten in Serang Banten Province.This study used a method of 2x2 factorials experiment with the design. The treatment is provided to present two methods of learning, they are the method of guided discovery and the method of demonstrations .This research is held in group b kindergarten in Serang Banten, from May until August 2014 with the sample which is taken through a method of multistage random sampling. The sample consisted of kindergarten students in Amalia and Al- Khautsar Kindergarten. The data was analyzed by using descriptive statistics, then the analysis and hypothesis testing requirements were analyzed by two lanes variance (Anova two-way).